2018
DOI: 10.1002/asia.201800814
|View full text |Cite
|
Sign up to set email alerts
|

Controllable 1D and 2D Cobalt Oxide and Cobalt Selenide Nanostructures as Highly Efficient Electrocatalysts for the Oxygen Evolution Reaction

Abstract: The relationship between controllable morphology and electrocatalytic activity of Co O and CoSe for the oxygen evolution reaction (OER) was explored in alkaline medium. Based on the time-dependent growth process of cobalt precursors, 1D Co O nanorods and 2D Co O nanosheets were successfully synthesized through a facile hydrothermal process at 180 °C under different reaction times, followed by calcination at 300 °C for 2 h. Subsequently, 1D and 2D CoSe nanostructures were derived by selenization of Co O , which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…The Se 3d spectrum of CoSe 2 (Figure 3d) revealed that it contained Se 2 2− ions in major proportion compared to Se 4+ as surface-oxidized SeO 2 and completely reduced Se 2− . 30,40,41,43,44 This has once again confirmed that the formed phase in the synthesis is CoSe 2 as predicted earlier from TEM analysis. Apart from this, both Figure 3b and Figure 3d 4a).…”
Section: Synthesis Of Coseosupporting
confidence: 86%
See 2 more Smart Citations
“…The Se 3d spectrum of CoSe 2 (Figure 3d) revealed that it contained Se 2 2− ions in major proportion compared to Se 4+ as surface-oxidized SeO 2 and completely reduced Se 2− . 30,40,41,43,44 This has once again confirmed that the formed phase in the synthesis is CoSe 2 as predicted earlier from TEM analysis. Apart from this, both Figure 3b and Figure 3d 4a).…”
Section: Synthesis Of Coseosupporting
confidence: 86%
“…Figure a is the high-resolution XPS spectrum of the Co 2p state of CoSeO 3 ·2H 2 O which showed the typical Co 2p 3/2 and Co 2p 1/2 doublet at 781.1 and 797 eV with their respective satellite peaks placed adjacent at slightly higher binding energy values. This indicated the presence of Co 2+ ions in CoSeO 3 ·2H 2 O as expected, and no Co 3+ ions were present. ,,, The Se 3d XPS spectrum (Figure b) upon deconvolution revealed that CoSeO 3 ·2H 2 O had almost all of its Se in the Se 4+ state (at 59.2 eV) with a minor amount of Se 2 2– ions. , This indicates that the chemical preoxidation of selenide was successful. Similarly, the exclusive presence of Co 2+ ions was witnessed with the Co 2p XPS spectrum (Figure c) of CoSe 2 as well.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Catalytic performance of our best sample is also compared with the standard RuO 2 and earlier reported cobalt-based electrocatalyst representing akin activity in terms of iR -corrected backward LSV scan (Table S2). This result also fortifies the bulk scale implementation of the Co 3 O 4 /Co 0.85 Se/Co 9 Se 8 framework as a commercial electrocatalyst for alkaline water oxidation purpose.…”
Section: Resultsmentioning
confidence: 66%
“…The satisfactory OER activity could be ascribed to the following factors: (i) The pre-electrocatalyst [Co­(NH 3 ) 4 CO 3 ]Cl contains abundant Co­(III), which is converted to CoOOH during the activation process. (ii) The enriched Co 3+ ions can not only increase the H 2 O molecules adsorption energy but also promote the deprotonation of OOH species to form O 2 . (iii) The 2D structure of activated [Co­(NH 3 ) 4 CO 3 ]Cl drastically increases the catalytic area and exposes more electrochemical active sites, thus facilitating the ion and electron diffusion during OER.…”
Section: Resultsmentioning
confidence: 99%